SP0180 Communication skills, an essential competency to make the difference in daily practice. (12th June 2018) - Nigil Haroon, N.; Szabo, E.; CHEUNG, A.M.; Inman, R.
Abstract : Background: Ankylosing spondylitis (AS) is associated with high risk of fractures. BMD, bone microarchitecture and strength are negatively affected in AS. TNF inhibitors such as etanercept, adalimumab, golimumab and infliximab are the mainstay of treatment in AS. However no data is available on the effect of TNF inhibitors on bone microarchitecture and strength. Objectives: This study aimed to assess the effect of TNF inhibitors on bone microarchitecture in patients with AS. Methods: AS was defined by Modified New York criteria. Areal BMD was measured by DXA. Volumetric BMD (vBMD) and bone microarchitecture were measured using highresolution peripheral quantitative CT (HRpQCT) at the radius and tibia at baseline and after one year of treatment with TNF inhibitors. Intake of calcium and vitamin D were optimised. Results: There were 31 subjects (58% men). Mean (+SD) age and BASDAI were 40+14 years and 4.1+2.1 respectively. Median duration of disease was 14 (IQ: 6.5–25.5) years. Mean duration of follow-up was 15 months. Areal BMD (n=22) at lumbar spine (1.053+0.235 vs. 1.049+0.202, p=0.89), total hip (0.944+0.152 vs. 0.912+0.164, p=0.5), and femoral neck (0.955+0.151 vs. 0.954+0.191, p=0.2) did not change significantly. HRpQCT (n=31) on follow-up demonstrated that total, trabecular and cortical volumetric BMD were unchanged at both radius and tibia (table 1). Also, HRpQCT based trabecular parameters such as trabecular number, thickness and separation, BV/TV and cortical parameters such as cortical porosity and thickness remained stable (table 1). FEA estimates of bone stiffness and stress tended to be lower at the radius on follow-up however these parameters were not significantly different at the tibia (table 1). Conclusions: This is the first study to document the changes in bone strength in AS patients with the use of TNF inhibitors. Treatment with TNF inhibitors might maintain bone microarchitecture at cortical and trabecular sites in patients with AS. Disclosure of Interest: N. Nigil Haroon Consultant for: AMGEN Canada, E. Szabo: None declared, A. CHEUNG Consultant for: AMGEN, ELI LILLY, R. Inman Grant/research support from: AMGEN, Consultant for: AMGE, ABBVIE, NOVARTIS, JANNSEN, MERCK